Liderazgo transformacional y su relación en el trabajo en equipo en los estudiantes de la carrera de Gestión de la Información Gerencial de la Universidad Técnica de Cotopaxi. (2022) - Sánchez Yela, Estefanía Pamela (2022)
This research project proposes the study of transformational leadership and its relationship in teamwork in students of the Management Information Management career at the Technical University of Cotopaxi (2022). With a mixed approach methodology, with a non-experimental descriptive research design. The population under study were the students of the career. Currently, transformational leadership is important within institutions because it helps to improve communication, to have self-confidence, fostering a commitment to meet the given objectives and have the ability to guide a work team, both academic and professional. labor. For the study, a validated instrument was applied that measures transformational leadership Multifactor Leadership Questionnaire (MLQ Short Form 5X), which consists of 4 components: idealized influence, inspirational motivation, individualized consideration, intellectual stimulation of 33 items: on the Likert scale . Obtaining as a result 52% of Management Information Management students do not have transformational leadership influencing intellectual stimulation due to lack of being innovative and creative.